Expression of asthma susceptibility genes in bronchial epithelial cells and bronchial alveolar lavage in the Severe Asthma Research Program (SARP) cohort. (13th September 2016) - Li, Xingnan; Hawkins, Gregory A.; Moore, Wendy C.; Hastie, Annette T.; Ampleford, Elizabeth J.; Milosevic, Jadranka; Li, Huashi; Busse, William W.; Erzurum, Serpil C.; Kaminski, Naftali; Wenzel, Sally E.; Bleecker, Eugene R.; et al.
Abstract: Objective : Genome-wide association studies (GWASs) have identified genes associated with asthma, however expression of these genes in asthma-relevant tissues has not been studied. This study tested expression and correlation between GWAS-identified asthma genes and asthma or asthma severity. Methods : Correlation analyses of expression levels of GWAS-identified asthma genes and asthma-related biomarkers were performed in cells from human bronchial epithelial biopsy (BEC, n = 107) and bronchial alveolar lavage (BAL, n = 94). Results : Expression levels of asthma genes between BEC and BAL and with asthma or asthma severity were weakly correlated. The expression levels of IL18R1 were consistently higher in asthma than controls or in severe asthma than mild/moderate asthma in BEC and BAL ( p < 0.05). In RAD50-IL13 region, the expression levels of RAD50, not IL4, IL5, or IL13, were positively correlated between BEC and BAL (ρ = 0.53, P = 4.5 × 10 −6 ). The expression levels of IL13 were positively correlated with IL5 in BEC (ρ = 0.35, P = 1.9 × 10 −4 ) and IL4 in BAL (ρ = 0.42, P = 2.5 × 10 −5 ), respectively. rs3798134 in RAD50, a GWAS-identified SNP, was correlated with IL13 expression and the expression levels of IL13 were correlated with asthma ( P = 0.03). rs17772583 in RAD50 was significantly correlated with RAD50 expression in BAL and BEC ( P = 7.4 × 10 −7 and 0.04) but was not associated with asthma. Conclusions : This is the first report studying the expression of GWAS-identified asthma genes in BEC and BAL. IL13, rather than RAD50, IL4, or IL5, is more likely to be the asthma susceptibility gene. Our study illustrates tissue-specific expression of asthma-related genes. Therefore, whenever possible, disease-relevant tissues should be used for transcription analysis.